Reversible Control of the Mn Oxidation State in SrTiO3 Bulk Powders - Mansoor, Haneen; Harrigan, William L.; Lehuta, Keith A.; Kittilstved, Kevin R. (Frontiers in Chemistry, 2019)
We demonstrate a low-temperature reduction method for exhibiting fine control over the oxidation state of substitutional Mn ions in strontium titanate (SrTiO3) bulk powder. We employ NaBH4 as the chemical reductant that causes significant changes in the oxidation state and oxygen vacancy complexation with Mn2+ dopants at temperatures <350°C where lattice reduction is negligible. At higher reduction temperatures, we also observe the formation of Ti3+ in the lattice by diffuse-reflectance and low-temperature electron paramagnetic resonance (EPR) spectroscopy. In addition to Mn2+, Mn4+, and the Mn2+ complex with an oxygen vacancy, we also observe a sharp resonance in the EPR spectrum of heavily reduced Mn-doped SrTiO3. This sharp signal is tentatively assigned to surface superoxide ion that is formed by the surface electron transfer reaction between Ti3+ and O2. The ability to control the relative amounts of various paramagnetic defects in SrTiO3 provides many possibilities to study in a model system the impact of tunable dopant-defect interactions for spin-based electronic applications or visible-light photocatalysis.